Use of Quarry Dust in the Binding Mortar and Its Effect on Mechanical Characteristics of Brick Masonry - Kosalya, S.; Arvinthan, P.; Sathiparan, N. (Universiti Tun Hussein Onn Malaysia Publisher’s Office, 2022)
The strength characteristics of masonry is greatly affected by the brick strength, mortar strength and bond between brick-mortar interface. Especially, binding mortar significantly affects the shear and flexural strength of the masonry. In conventional masonry construction, river sand or natural sand is mixed with cement and used as binding mortar. However, due scarcity of good quality river sand, the extensive focus is on finding alternative materials for river sand for construction purposes. Quarry dust is one of the best alternatives for river sand, which can be used as fine aggregates in binding mortar. This study investigates the strength characteristic of the masonry made of quarry dust incorporated binding mortar instead of conventional cement-sand mortar. The binding mortar with four different river sand replacement levels of 0%, 33.3%, 66.7% and 100% quarry dust, was used for construction masonry. Compression test, direct shear test and cross-couplet test were conducted to evaluate the strength characteristic. The test results revealed that compressive, shear and bond strength of masonry was improved with increased quarry dust content in the binding mortar.
Keywords: Masonry; Binding mortar; River sand; Quarry dust; Characteristic strength